Microwave‐Induced Metal Dissolution Synthesis of Core–Shell Copper Nanowires/ZnS for Visible Light Photocatalytic H2 Evolution. Issue 22 (24th April 2019) - Xiao, Shuning; Dai, Wenrui; Liu, Xiaoyan; Pan, Donglai; Zou, Hangjun; Li, Guisheng; Zhang, Guoqiang; Su, Chenliang; Zhang, Dieqing; Chen, Wei; Li, Hexing
Abstract: A microwave‐induced metal dissolution strategy is developed for in situ synthesis of copper nanowires/ZnS (CuNWs/ZnS) hybrids with core–shell structure. The CuNWs are used as microwave antennas to create local "super‐hot" surfaces to further initiate ZnS crystallization with full coverage on CuNWs. With the help of S 2−, the hot metal surface further results in the CuNWs dissolution with promoted Cu + diffusion and incorporation into the ZnS lattice. With the narrowed bandgap of ZnS and the strongly coupled interface between CuNWs and ZnS created by microwaves, the as‐prepared hybrid composites exhibit an enhanced activity and stability in visible light for the photocatalytic H2 evolution. The corresponding H2 evolution rate reaches up to 10722 µmol h −1 g −1 with apparent quantum efficiency (AQE) of 69% under 420 nm LED irradiation, showing a remarkably high AQE among the noble‐metal free visible light‐driven photocatalysts and demonstrating a promising potential in practical applications to deal with the energy crisis. Abstract : A CuNWs/ZnS catalyst is synthesized by a microwave‐induced metal dissolution strategy . Microwave‐induced super‐hot metal surface facilitates ZnS crystallization and drives the metal dissolved to dopant. With the optimized interfacial and bandgap coupling, it shows the highest H2 evolution rate of 10722 µmol h −1 g −1 among the noble‐metal‐free photocatalysts under visible light irradiation.